The Polysemic Nature Of Military Terms - Dilnoza Aminova (Zien Journals, 2024)
This paper delves into the polysemic nature of military terminology, exploring its multifaceted meanings within and beyond the armed forces. Military language, known for its precision and discipline, conceals a complex web of polysemy, enabling nuanced communication and reflecting the dynamism of linguistic evolution. Through a review of seminal works and an analysis of key terms, this study highlights how military terminology adapts to technological advances and societal shifts, permeating civilian discourse. The investigation reveals that the layered meanings of military terms not only facilitate intramilitary clarity but also enrich civilian language, embodying the interplay between military culture and broader linguistic trends.
Keywords: Military terminology; linguistic evolution; polysemy